Tax Consideration in Partnership Agreements. - Bogart, Fred O. (The Accounting Review, 1965)
The code and regulations concerning partnership activities are among the most complex laws and rules in the field of taxation. The article focuses on the effects of the U.S. Internal Revenue Code while discussing the importance of the tax effects to be considered during the formulation of original partnership agreements and later timely modification thereof which can eliminate some inequities that might arise among partners. An agreement should be arrived at among partners as to the treatment of certain aspects of contributed property. If the agreement is silent as to the depreciation of the contributed property, the depreciation would be treated as if the property had been purchased by the partnership. Cash payments in liquidation of a partner's interest in a partnership or to successors in interest of a deceased partner's interest can raise some tax consequences. A distinction in the tax law between payments in liquidation of a partner's interest in partnership property and other liquidating payments should be carefully considered before an agreement is reached between a retiring partner and the remaining partners of the partnership.